A Large Source of Atomic Chlorine From ClNO2 Photolysis at a U.K. Landfill Site - Thomas J. Bannan; M. Anwar H. Khan; Michael Le Breton; Michael Priestley; Stephen D. Worrall; Asan Bacak; Nicholas A. Marsden; Douglas Lowe; Joe Pitt; Grant Allen; David Topping; Hugh Coe; et al. (Geophysical Research Letters)
Abstract Nitryl chloride (ClNO2) acts as a source of highly reactive chlorine atoms as well as an important NOx reservoir. Measurements of ClNO2 at an operational U.K. landfill site are reported here for the first time. A peak concentration of 4 ppb of ClNO2 was found with a peak mean nighttime maximum of 0.9 ppb. Using models based upon the photolysis of observed ClNO2 and atmospheric chlorine chemistry, chlorine atom concentrations reaching in excess of 1.20 × 105 molecules/cm3 in the early morning following sunrise are calculated. These concentrations are approximately 10 times higher than previously reported in the United Kingdom, suggesting a significant impact on the oxidizing capacity around such sites. Given the ubiquity of landfill sites regionally and globally, and the large abundances of Cl atoms from the photolysis of ClNO2, chlorine chemistry has a significant impact on ozone formation and volatile organic compounds oxidation as shown by WRF‐Chem modeling.